Effect of Chengal Wood (Neobalanocarpus heimii) on Physicochemical and Antimicrobial Properties of Coconut Sap (Cocos nucifera). Issue 1 (August 2020) - Saidan, Noor Hafizoh; Afiq Kartayasa, Mohd Amir; Mohd Lokman, Nur Ilham Atiqah; Ab Llah, Nurul Fadzlin; Nor, Maryana Mohamad; Mokhtar, Seri Intan; Pahirul Zaman, Khomaizon Abdul Kadir; Sidek, Nik Marzuki; Ridzuan Hamil, Mohd Shahrul
Abstract: Coconut sap from Cocos nucifera could be obtained from the coconut flower, and it is quite a popular fresh drink in Malaysia. Due to microbial activity, coconut sap may change to alcoholic and acidic by spontaneous fermentation. Traditionally, chengal wood chips ( Neobalanocarpus heimii ) have been added in coconut sap to slow down the fermentation process. This research aims to evaluate the physicochemical properties (pH, total acidity, total soluble solids, colour), volatile organic compounds (VOCs) and antimicrobial properties of coconut sap with and without the presence of chengal wood chips for ten weeks at 4 °C and 25 °C storage temperatures. The pH value of both samples was between 3.60 ± 0.01 to 6.66 ± 0.04. Total acidity ranged from 0.29 ± 0.11% to 4.26 ± 0.25%. Total soluble solids in both samples were around 8.3 ± 0.05 to 17.3 ± 0.05 °Brix. Colour analysis was also carried out based on the lightness value. Eighteen of VOCs were found in coconut sap with chengal wood chips versus 20 compounds without the chengal wood chips. Coconut sap with chengal wood chips kept at 4 °C had the lowest total plate count (1.19 x 104 - 1.78x106 CFU/mL) at week one until week seven, while total plate count of coconut sap without chengal wood chips was recorded as too numerous to count (TNTC) throughout the weeks. Chengal wood chip extracts inhibited the growth of Staphylococcus aureus, Escherichia coli, Candida albicans, and Aspergillus brasiliensis, as shown by a clear zone of inhibition. In conclusion, the presence of chengal wood in coconut sap has helped to slow down the fermentation process and inhibit the growth of microorganisms. Hence it can help to prolong the shelf life of coconut sap.